Concept and Role of Plant Ideotypes in Sustainable Agriculture - Naik, M. Ramesh; Alekhya, V.; Vidyavathi, L.; Teja, R. Ravi; Ramanjaneyulu, A. V.; Lakshmi, D. Vijaya (Chronicle of Bioresource Management, 2025)
Sustainable agriculture is vital for global food security amid climate change, pandemics, and geopolitical challenges. The ideotype concept, introduced by Donald (1968), promotes breeding of crop varieties that are high-yielding, resource-efficient, and resilient. An ideotype refers to a model plant with specific traits suited to a particular environment or farming system. Over time, this concept has expanded to include ideotypes tailored to isolation, stress, market, climate, competition, and edaphic conditions. Ideal ideotypes exhibit traits like high photosynthetic efficiency, optimal architecture, synchronized maturity, and tolerance to biotic and abiotic stresses. Their development involves a blend of conventional breeding and modern tools such as marker-assisted selection, genetic engineering, functional genomics, crop modeling, and high-throughput phenotyping. Ideotype-based breeding enhances yield stability, reduces input use, and minimizes environmental impact. While challenges remain, ideotypes offer a strategic path toward resilient and sustainable agricultural systems for future food security.